The A/R /Tography as an initial methodological perspective in artistic mediation programs based on Art Therapy - González-García, Ricardo (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2020)
The present paper explores the A/R/Tgraphic perspective as a method of qualitative inquiry that leads the artist-researcher-teacher to consider the fields of artistic mediation, including intervention programs based on Art Therapy, as spaces where he/she could collaborate. Without encouraging any professional intrusion, and respecting the tasks assigned to each agent, the relationship between A/R/Tography and Art Therapy is contemplated, as a likely interdisciplinary conversation within the context of artistic mediation, A dialogue that can allow art therapy intervention to take into account the advantages of A/R/Tography, and its researcher capacities in the development process in these kind of programs in which pedagogy plays a fundamental role. It is for that reason, and from an anthropological view, that it will be necessary to distinguish the specific objectives of each agent, so the artistic mediation become a possible unifying environment of both fields. In this line of investigation about discerning what fields of knowledge belongs to each agent involved, a diagram is design in order to show the wide confluence among different, but related disciplines that can be deployed in therapeutic interventions in artistically mediated contexts, and how it could be become a qualitative research. This work supposes a complex vision due to consider multitude of disciplinary interrelations, but its ultimate objective is to emphasize the common points about symbolizing processes that take place in that areas that consider art as a vehicle in intervention-research programs